Agency development of Dai-Ichi Life Insurance Company - Vu, Ba Tuyen; Swierczek, F.W.; Bechter, Clemens; Nguyen, Cong Thanh (Pathumthani : Asian Institute of Technology, 2007)
During the past two decades Vietnam has experienced a rapid growth in the economy, which has stimulated the development of the Life Insurance Industry of Vietnam. The Industry has been remarkably developed through the foreign-invested entrants. Dai-ichi Life Insurance Company of Vietnam (DLVN) entered through the acquisition of Bao Minh CMG Life Insurance Company (BMCMG) in January 2007. This research study conducts an analysis of the 7s - model by McKinsey Consulting, which helps identify the quality level of the agency force of DLVN, it examines the performance of its competitors by identifying their key success factors. To assess the quality of DLVN agency force, in addition to the secondary data, personal interviews has been undertaken with the DLVN{u2019}s existing agency managers. This research has revealed the most outstanding concern, an impeding factor of DLVN. This is the low quality of the agency force. Changes required include selection, maximization of agency force potential through objectively result-oriented training, field management development, performance management system, structured compensation program to reward and the use of technology to support agent productivity growth and development.
A research study submitted in partial fulfillment of the requirements for the degree of Master of Business Administration, School of Management
Keywords: Dai-Ichi Life Insurance Company; Insurance, Life